Obstructive sleep apnea syndrome - from subtle intervention to orthognathic surgery: Literature review (Research, Society and Development, 2025)
Objective: The aim of this study is to provide a literature review on therapeutic approaches in OSAS, highlighting the wide range of available interventions, from subtle intervention to orthognathic surgery. Methodology: Clinical, laboratory and literature review articles that addressed the topic in question were included. The research used articles in Portuguese and English. To prepare the review, a search was performed in scientific databases, such as SciELO, PubMed and Google Scholar. Literature Review: Obstructive Sleep Apnea Syndrome (OSAS) is a chronic and disabling respiratory disorder that presents worrying rates of morbidity and mortality. The classification of OSAS is based on the nature of the apnea (central, obstructive or mixed) and the apnea-hypopnea index (AHI), which represents the number of apneic events per hour of sleep. The obstructive nature of the disease results from obstruction of the upper airways during sleep. This syndrome, which is often underdiagnosed, is associated with several factors, including craniofacial alterations, harmful lifestyle habits, and anatomical, postural, dietary, and hormonal aspects. Its diagnosis is obtained through anamnesis, intraoral examination, radiographic examinations, questionnaires, and polysomnography. Conclusion: Subtle interventions may include changes in dietary and medication habits; for mild and moderate cases, treatments such as oral devices and CPAP are effective, considering patient compliance. For severe cases, orthognathic surgery appears as an efficient option, providing significant improvements in the upper airway, reducing apnea and hypopnea rates and improving the patient's quality of life.